Grape Polyphenols Attenuate Diet-Induced Obesity and Hepatic Steatosis in Mice in Association With Reduced Butyrate and Increased Markers of Intestinal Carbohydrate Oxidation - Mezhibovsky, Esther; Knowles, Kim A.; He, Qiyue; Sui, Ke; Tveter, Kevin M.; Duran, Rocio M.; Roopchand, Diana E. (Frontiers in Nutrition, 2021)
A Western Diet (WD) low in fiber but high in fats and sugars contributes to obesity and non-alcoholic fatty liver disease (NAFLD). Supplementation with grape polyphenols (GPs) rich in B-type proanthocyanidins (PACs) can attenuate symptoms of cardiometabolic disease and alter the gut microbiota and its metabolites. We hypothesized that GP-mediated metabolic improvements would correlate with altered microbial metabolites such as short chain fatty acids (SCFAs). To more closely mimic a WD, C57BL/6J male mice were fed a low-fiber diet high in sucrose and butterfat along with 20% sucrose water to represent sugary beverages. This WD was supplemented with 1% GPs (WD-GP) to investigate the impact of GPs on energy balance, SCFA profile, and intestinal metabolism. Compared to WD-fed mice, the WD-GP group had higher lean mass along with lower fat mass, body weight, and hepatic steatosis despite consuming more calories from sucrose water. Indirect and direct calorimetry revealed that reduced adiposity in GP-supplemented mice was likely due to their greater energy expenditure, which resulted in lower energy efficiency compared to WD-fed mice. GP-supplemented mice had higher abundance of Akkermansia muciniphila, a gut microbe reported to increase energy expenditure. SCFA measurements in colon content revealed that GP-supplemented mice had lower concentrations of butyrate, a major energy substrate of the distal intestine, and reduced valerate, a putrefactive SCFA. GP-supplementation also resulted in a lower acetate:propionate ratio suggesting reduced hepatic lipogenesis. Considering the higher sucrose consumption and reduced butyrate levels in GP-supplemented mice, we hypothesized that enterocytes would metabolize glucose and fructose as a replacement energy source. Ileal mRNA levels of glucose transporter-2 (GLUT2, SLC2A2) were increased indicating higher glucose and fructose uptake. Expression of ketohexokinase (KHK) was increased in ileum tissue suggesting increased fructolysis. A GP-induced increase in intestinal carbohydrate oxidation was supported by: 1) increased gene expression of duodenal pyruvate dehydrogenase (PDH), 2) a decreased ratio of lactate dehydrogenase a (LDHa):LDHb in jejunum and colon tissues, and 3) decreased duodenal and colonic lactate concentrations. These data indicate that GPs protect against WD-induced obesity and hepatic steatosis by diminishing portal delivery of lipogenic butyrate and sugars due to their increased intestinal utilization.